Including child's voice. - Rembach, Lauren Ann (My University, 2013)
In this research I present a conceptual analysis of conceptions of child and childhood. These conceptions largely point to a worldview that sees childhood as a universal construct, and I argue that the conceptualisation of childhood differs in cultural, historical, political, philosophical and developmental psychology domains. I argue that what is common to many of these discourses is that concepts and conceptions of child and childhood reveal differences in how one views the dichotomy between adult-child. I also go on to discuss the implications of these conceptions of child, childhood and child’s voice in a school context. The many discourses of childhood are underpinned by beliefs and assumptions about the experience and purpose of childhood, and therefore inform policies and shape educational practice. How a community or society conceptualises childhood is implied in the practices and policies of that community or society. While some researchers agree there is a need to reconceptualise childhood, consensus dissolves around the diverse definitions of child and childhood and how child’s voice should be included in educational contexts. I explore the positioning of child in historical and contemporary constructs and discuss emerging trends of how child and childhood is conceptualised. I examine arguments with regards to opening up debates that suggest that if child and childhood is reconceptualised there is potential to move beyond normative policies, practices and pedagogies that remain entrenched in our current educational contexts. Drawing on my own experiences in working with children I use these experiences to argue that there has been a shift in my own thinking about child and offer through the literature that many authors suggest alternative constructions of child as a being, with capabilities of giving voice. To consider what the concept voice means in terms of including child’s voice in educational contexts, links emerge with the discourse of children’s rights and the diverse and complex conceptualisations of child and childhood. Researchers, educators and policy-policy makers need to examine their meanings of child and childhood and critically engage with the assumptions thereof in order to reconceptualise hegemonic dominance of policies and practices based on one definition of child. Children’s rights have been part of a legal framework, while understanding of what it means to be child run deeper into theories of childhood underpinned by moral, socio- economic and political agendas that are part of child’s world. Advocates of the children’s rights discourse argue that a contemporary crisis in childhood has emerged, causing a power struggle between adult-child relationships, as child is acknowledged as a powerful individual whose experiences are to be taken seriously.
Keywords: Child; Childhood; Children's rights; Child's voice